Circular economy of shopping bags in emerging markets: A demographic comparative analysis of propensity to reuse plastic bags versus cotton bags and paper bags. Issue 1 (31st December 2023) - Mukucha, Paul; Jaravaza, Divaries Cosmas; Nyengerai, Sarah
Abstract: This study seeks to profile the shoppers' propensity to reuse shopping bags and the type of shopping bags they reuse on the basis of demographics. The study used an observation method to record the consumers' shopping habits and a short questionnaire to record the participants' demographics. A binary regression analysis and a multinomial regression analysis were used to analyse data. The results indicated that the mature aged, women, and low income shoppers were more likely to practice reuse of plastic shopping bags than their respective counterparts. There were no statistically significant differences in the likelihood of young aged shoppers compared to mature aged shoppers and low income shoppers compared to high income shoppers using cotton bags than plastic bags. There were also no statistically significant differences in the likelihood of young aged shoppers compared to mature aged shoppers and male shoppers compared to female shoppers using paper bags than plastic bags. However, the results indicated a statically significant result in how males compared to females differed in their using of cotton bags than plastic bags and a statistically significant result in how low income shoppers compared to high income shoppers differed in their use of paper bags than plastic bags.